Correlation between peripheral immature platelet level and coronary immature platelet levels in coronary artery disease: an observational study in cardiac referral centre in East Java, Indonesia - Dimas Rio Balti; Andrianto; Ryan Enast Intan; Firas Farisi Alkaff (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the correlation between peripheral and coronary immature platelet, and factors that may predict coronary immature platelet levels. Method: The cross-sectional, observational, analytical study was conducted at the Cardiovascular Diagnostic and Intervention Centre of Dr Soetomo General Academic Hospital, Surabaya, Indonesia, from November 2017 to January 2018, and comprised patients of either gender with coronary artery disease. Peripheral and coronary blood samples were retrieved during coronary catheterisation. Immature platelet fraction was acquired by examining whole blood samples analysed through automated flow cytometry. Relationship between peripheral and coronary immature platelet fractions and counts were analysed using parametric correlation test, followed by linear regression analysis model of variables that influenced coronary immature platelet fraction. The statistical analysis was carried out using SPSS Statistics for Windows, Version 25.0 (IBM Corp, Armonk, NY, USA). Results: Of the 70 patients, 55(78.6%) were males and 15(21.4%) were females. The overall mean age was 57±5.32 years. There were 35(50%) patients with a history of smoking, and 34(48.6%) had hypertension and dyslipidaemia. Mean peripheral immature platelet fraction was 3.86±1.84% and mean coronary immature platelet fraction was 3.63±1.7%. There was a robust positive and significant correlation (r=0.882; p<0.001) between immature platelet levels in peripheral and coronary blood. Peripheral immature platelet and glycated haemoglobin >7.5 were independent predictors of coronary immature platelet (p=0.001). Conclusion: There was a strong correlation between immature platelet levels in peripheral and coronary blood. Key Words: Haemoglobin, Platelets, Coronary vessels, Heart.